Priority-based message forwarding and query processing in opportunistic wireless sensor network - Yong-xuan LAI; Zi-yu LIN (Tongxin xuebao)
A priority-based algorithm called PBQ was proposed for the query forwarding and processing in opportunistic wireless sensor network.Through the user-defined query priorities,the proposed algorithm properly selects the relay nodes and controlls the forwarding and the amount of messages.Meanwhile,the query priorities were adjusted dynamically so that the query results could be forwarded back to the source node of the query quickly and the residual query request messages could be cleaned up from the network,saving lots of unnecessary transmissions and improving the overall utility of query processing.Simulating results show that PBQ could effectively improve the success rate of queries,and reduce the cost and delay of query processing in opportunistic wireless sensor network.